Jesuit Missionary Aleni’s Argumentation Strategy on the Concept of Common Sense: Focusing on the Analysis of Xingxue Cushu - Qi Zhao (Religions)
In the late Ming Dynasty, Jesuit missionary Giulio Aleni introduced Western classical psychology to China, with the theory of the sensitive soul being his core focus. Scholars have conducted in-depth analyses of the textual sources, fundamental theories and pivotal influences of Xingxue cushu concerning Aleni’s theory of the sensitive soul. Nevertheless, there is a lack of research in academia on the essence of common sense. In Aleni’s Xingxue cushu, common sense not only determines the essence of a sensitive soul but also builds a bridge between a sensitive soul and rational soul. Consequently, common sense is a crux in Aleni’s soul theory. As far as the purpose is concerned, this article combines macro and micro perspectives, exploring Aleni’s argumentation strategy on the concept of common sense. Although Aleni regards common sense as the internal sense of human beings, he starts from the principle of wholeness in Xingxue cushu and regards common sense as the whole of the five external senses, indicating that the principle of wholeness is not contradictory to the principle of internality in the category of common sense.